The Influence of Growth Mindset on the Mental Health and Life Events of College Students - Tao, Weidong; Zhao, Dongchi; Yue, Huilan; Horton, Isabel; Tian, Xiuju; Xu, Zhen; Sun, Hong-Jin (Frontiers in Psychology, 2022)
Growth mindset refers to our core beliefs that we can develop talents and abilities through practice, which influences our thoughts and behavior. Growth mind-set has been studied in a variety of fields, including education, sports, and management. However, few studies have explored whether differences exist in in mental health and life events between groups of college students with different types of growth mindsets. In order to explore whether differences in individuals’ growth mindsets influence college students self-reported mental health, data was collected from 2,505 freshmen using the Growth Mindset Scale, Adolescent Self-rating Life Events Checklist, and SCL-90 Scale. Findings revealed that the growth mindset group scored significantly lower on ‘mental health issues’ and ‘stress due to life events’ than the fixed mindset group. Our findings suggest that individuals with a growth mindset are less likely to suffer from mental health problems than individuals with a fixed mindset.